Breaches in the Boardroom: Organizational Identity and Conflicts of Commitment in a Nonprofit Organization - Golden-Biddle, Karen; Rao, Hayagreeva (Organization Science, 1997)
In recent years, agency theory has substantially influenced research on corporate governance. Organizational sociologists have critiqued the agency theory model of boards as limited and have studied how the functioning of boards is shaped by structural, political, and cognitive contexts. Building on their work, this paper empirically studies the cultural embeddedness of boards in a nonprofit organization called Medlay. It shows how organizational identity—the members' shared beliefs about the central, enduring, and distinctive characteristics of the organization—influences the construction and enactment of the director's role and shapes interactions among board members and managers. The findings demonstrate that the role of the director is shaped by Medlay's Janus-faced identity, as both a volunteer-driven organization and a family of friends; directors see themselves as vigilant monitors and as friendly, supportive colleagues. The findings also portray how some board members' scrutiny of the budget, including “lavish” travel expenditures, surfaces the contradictions in Medlay's identity, and creates conflicts for directors. Should board members take manager to task and thereby exercise vigilance and uphold the ideal of volunteer control, or should they safeguard the principle of friendship and avoid all conflict? An influential subset of directors and top managers resolved the budget issue and preserved Medlay's identity by using different “face-saving” strategies to make directors feel that they had been vigilant, and to affirm sentiments of cooperation. More generally, this study extends the literature on corporate governance by showing how organizational identity influences the construction and enactment of the director's role. It introduces the idea of “conflicts of commitment,” a form of intra-role conflict that arises when directors are besieged by conflicting aspects of the organization's identity. When actions occur that breach the expected role performance of board members, latent contradictions in the organizational identity emerge, and directors are faced with the conflict of upholding one dimension of identity while undermining the other. The study also contributes to research on organizational identity by proposing a model of how organizational and individual identities shape the board role through the processes of identification and action, and how a hybrid identity generates the potential for intra-role conflict.